Pemberdayaan Masyarakat melalui Sistem Informasi Digital Wisata Hiu Paus untuk Mendukung Pengelolaan Pariwisata Berkelanjutan di Desa Botubarani - Nur Oktavin Idris; Rosbin Pakaya; Moh. Hidayat Koniyo; Fuad Pontoiyo (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
The whale shark ecotourism potential in Botubarani Village is an economic pillar for the local community, yet its management remains conventional. This triggers disorderly boat queues, vulnerable revenue-sharing records, and suboptimal conservation education. This community service aims to empower managers through the development of a website-based Digital Information System. The implementation method includes needs analysis (observation and interviews), ERD design, system development, implementation, and training. The result is a comprehensive digital platform featuring public information, digital registration, whale shark monitoring, and tourism management. The system's implementation has successfully reduced ticket service time, organized boat queues, and made financial data recapitulation more transparent. Evaluation using a Likert scale shows a very high level of user satisfaction regarding ease of use, interface design, and information clarity. In conclusion, this digital transformation strengthens effective, transparent, and sustainable ecotourism governance in Botubarani Village.